Evaluating a novel vertical traction device for early closure in open abdomen management: a consecutive case series - Dohmen, J.; Weissinger, D.; Peter, A. S. T.; Theodorou, A.; Kalff, J. C.; Stoffels, B.; Lingohr, P.; von Websky, M. (Frontiers in Surgery, 2024)
In emergency surgery, managing abdominal sepsis and critically ill patients with imminent abdominal compartment syndrome (ACS) using an open abdomen (OA) approach has become standard practice for damage control. To prevent significant complications associated with OA therapy, such as abdominal infections, entero-atmospheric fistula (EAF), and abdominal wall hernia formation, early definitive fascial closure (DFC) is crucial. This study aims to assess the feasibility of a novel device designed to facilitate early fascial closure in patients with an open abdomen.Methods Between 2019 and 2020, nine patients undergoing open abdomen management were enrolled in this study. All patients were treated using vertical mesh-mediated fascial traction combined with a novel vertical traction device (VTD). Data from these cases were collected and retrospectively analyzed.In this study, all patients were treated with OA due to impending ACS. Three patients died before achieving DFC, while the remaining six patients successfully underwent DFC. The mean number of surgical procedures after OA was 3 ± 1, and the mean time to DFC was 9 ± 3 days. The use of the VTD in combination with negative pressure wound therapy (NPWT) resulted in a 76 % reduction in fascia-to-fascia distance until DFC was achieved. The application of the VTD did not affect ventilation parameters or the Simplified Acute Physiology Score II (SAPS II), but intra-abdominal pressure (IAP) was reduced from 31 ± 8 mmHg prior to OA to 8.5 ± 2 mmHg after applying the device. The primary complication associated with the device was skin irritation, with three patients developing skin blisters as the most severe manifestation.Overall, the novel VTD appears to be a safe and feasible option for managing OA cases. It may reduce complications associated with OA by promoting early definitive fascial closure.